Macrophage phenotype and bioenergetics are controlled by oxidized phospholipids identified in lean and obese adipose tissue - Serbulea, Vlad (Proc Natl Acad Sci U S A, 2018)
Adipose tissue macrophages (ATMs) adapt their metabolic phenotype either to maintain lean tissue homeostasis or drive inflammation and insulin resistance in obesity. However, the factors in the adipose tissue microenvironment that control ATM phenotypic polarization and bioenergetics remain unknown. We have recently shown that oxidized phospholipids (OxPL) uniquely regulate gene expression and cellular metabolism in Mox macrophages, but the presence of the Mox phenotype in adipose tissue has not been reported. Here we show, using extracellular flux analysis, that ATMs isolated from lean mice are metabolically inhibited. We identify a unique population of CX3CR1(neg)/F4/80(low) ATMs that resemble the Mox (Txnrd1(+)HO1(+)) phenotype to be the predominant ATM phenotype in lean adipose tissue. In contrast, ATMs isolated from obese mice had characteristics typical of the M1/M2 (CD11c(+)CD206(+)) phenotype with highly activated bioenergetics. Quantifying individual OxPL species in the stromal vascular fraction of murine adipose tissue, using targeted liquid chromatography-mass spectrometry, revealed that high fat diet-induced adipose tissue expansion led to a disproportional increase in full-length over truncated OxPL species. In vitro studies showed that macrophages respond to truncated OxPL species by suppressing bioenergetics and up-regulating antioxidant programs, mimicking the Mox phenotype of ATMs isolated from lean mice. Conversely, full-length OxPL species induce proinflammatory gene expression and an activated bioenergetic profile that mimics ATMs isolated from obese mice. Together, these data identify a redox-regulatory Mox macrophage phenotype to be predominant in lean adipose tissue and demonstrate that individual OxPL species that accumulate in adipose tissue instruct ATMs to adapt their phenotype and bioenergetic profile to either maintain redox homeostasis or to promote inflammation.